Cultural Competence in the Care of Muslim Patients and Their Families - Attum, Basem; Hafiz, Sumaiya; Malik, Ahmad; Shamoon, Zafar (StatPearls, 2025)
Muslims constitute large proportions of populations across both Muslim-majority countries and otherwise. Muslims are considered to be the fastest-growing religious group in the world. Knowledge of the cultural and spiritual values of Muslims is critical in providing healthcare services to them. Important differences include diet, ideas of modesty, privacy, touch restriction, and alcohol intake restriction. Globally, Muslims represent substantial portions of society, and Islam remains the fastest-growing religion in the world. It is highly likely that a healthcare professional will care for a Muslim patient during his or her career. The Muslim faith encompasses several ethnicities with diverse views regarding illness and healthcare. As a result, the care of Muslim patients provides challenges for many non-Muslim healthcare providers. The Islamic faith can influence decision-making, family dynamics, health practices, risks, and the use of healthcare. Understanding Islamic beliefs will assist healthcare professionals in delivering appropriate health care in a culturally sensitive manner. This can be accomplished by understanding religious implications, perspectives on family, health, illness, diet, the influence of traditional medicine, and privacy concerns. All health practitioners should be able to provide culturally competent care. When providing care to Muslim patients, it is important to understand the impact the Islamic faith has on the provision of healthcare. Healthcare professionals need to be aware of privacy and touch issues, dietary practices, and unacceptable medicines. When healthcare professionals interact with Muslim patients, they should follow certain guidelines whenever possible. This includes minimizing eye and physical contact between a healthcare worker and a patient of the opposite gender when possible. Furthermore, male doctors may have to communicate through a spouse if the patient is female. For example, if a male healthcare professional is talking to or asking questions of a female patient while her partner is in the room, but the patient does not respond, the healthcare professional should ask the patient if she would prefer he talk to the partner. This may clear up any confusion and is usually not offensive. During a physical exam, it is desirable to have the healthcare professional be of the same sex. Obviously, there will be circumstances in which this will not be possible. In these scenarios, having a third person in the room that is the same gender as the patient should comfort the patient. If a person of the opposite gender must perform the physical exam, the general rule of thumb is to inform the patient that an article of clothing must be removed for the examination, but it will be immediately returned. This minimizes exposure and tells the patient of the reasoning for removing any articles of clothing. In men, beards are religiously symbolic, and most men will avoid shaving unless it is essential. It is common knowledge that women dress modestly. Men are often dressed to the knees or past the knees as well. There is an impression that women dress modestly compared to men; however, many men follow many of the same rules of modesty. During Ramadan, the Holy Month of Islam, healthcare professionals should be particularly culturally sensitive and respectful. Clinicians who understand Muslim religious practices will be better equipped to provide appropriate, individualized care for Muslim patients. Obstacles to Medical Care The Muslim population is growing significantly worldwide. Cultural and religious background influence an individual's attitudes, behaviors, and beliefs toward health, illness, and the provision of healthcare may present obstacles to the healthcare this population receives. Due to perceived restrictions in medical care, the Muslim population may be at an increased risk for several diseases. These limitations may include gender preference of healthcare providers, modesty, and misconception about what causes certain illnesses. These limitations may develop as a result of Islamic cultural beliefs and practices. Other barriers may be due to the complexity of the health care system and the lack of culturally competent medical services and professionals. Health professionals should be aware of cultural and religious factors that help provide culturally competent and appropriate promotion and education of health services to the Islamic population. Health professionals must be educated about Islamic teachings to appropriately encourage healthy behaviors and provide quality care to their Islamic patients.